Responding to the Call to Curate: Digital Curation in Practice at Penn State University Libraries - Patricia Hswe; Michael J. Furlough; Michael J. Giarlo; MairÃ©ad Martin (International Journal of Digital Curation, 2011)
This paper describes how the Pennsylvania State (Penn State) University Libraries and the universityâ€™s central information technology organization, Information Technology Services, are putting into practice key tenets of digital curation through the newly established Content Stewardship program, a joint strategic initiative to implement stewardship services for the university. First, we provide an account of the planning, preparation, and prototyping that informed the initial year of the program. Second, we report on the hiring of a Digital Collections Curator and a Digital Library Architect and how they are advancing the program by putting digital curation into practice, which includes the work of community building. Finally, we address the organizational context of curation in practice, in particular with respect to the challenges of starting and sustaining a stewardship services program for all of Penn State.